Derivative Spectrophotometric Determination of Iron(II) Using Diacetylmonoxime Benzoyl Hydrazone - Devanna, N.; Sateesh, K.B.; Chandra Sekhar, K.B. (Asian Journal of Chemistry, 2016)
Diacetylmonoxime benzoyl hydrazone is a chromogenic reagent for the determination of Fe(II) and gives a yellow coloured water-soluble complex with Fe(II) in acidic buffer medium (pH 6.25). The molar absorptivity and Sandell’s sensitivity of the complex at lmax 360 nm is found to be 1.25 × 104 L mol–1 cm–1 and 0.0045 μg/cm2 of Fe(II) respectively. Beer's law validity range is from 0.11–2.24 μg/mL. Iron(II) gives 1 : 1 (M : L) complex with diacetylmonoxime benzoyl hydrozone and stability constant of the complex is 1.1 × 104. The developed direct and first order derivative spectrophotometric method was employed for the determination of iron in alloy samples and effect of various diverse ions is also studied.